INFORMATION TECHNOLOGY SOLUTIONS OFONLINE MAPSERVERS (PANGEEA, 2025)
Operation and structure of various map hosting websites and databases were examined. Based on my experience, the OpenStreetMap map was selected and used to create the website and geoinformatics database. The completed application can be used in international, multilingual research and helps to collect data on geoinformatics research on fear of crime. The application is currently available in four languages. Stores line and polygon type data in GeoJSON format. Data can be exported in Excel compatible format.
Keywords: OpenStreetMap; Shapefiles; GeoJSON; Leaflet; Digital maps